2016
DOI: 10.1016/j.plaphy.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

The stay-green phenotype of TaNAM-RNAi wheat plants is associated with maintenance of chloroplast structure and high enzymatic antioxidant activity

Abstract: SummaryTaNAM transcription factors play an important role in controlling senescence, which in turn, influences the delivery of nitrogen, iron and other elements to the grain of wheat (Triticum aestivum) plants, thus contributing to grain nutritional value. While lack or diminished expression of TaNAMs determines a stay-green phenotype, the precise effect of these factors on chloroplast structure has not been studied. In this work we focused on the events undergone by chloroplasts in two wheat lines having eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Currently, a broadly accepted perspective is that higher N levels of leaves are associated with delayed leaf senescence, which confers improved drought tolerance [11,36,37]. The decrease of yield between drought and nondrought stress increased with increasing N treatment rates.…”
Section: Yield and N Use Efficiency Of Maize Subjected To Drought Undmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a broadly accepted perspective is that higher N levels of leaves are associated with delayed leaf senescence, which confers improved drought tolerance [11,36,37]. The decrease of yield between drought and nondrought stress increased with increasing N treatment rates.…”
Section: Yield and N Use Efficiency Of Maize Subjected To Drought Undmentioning
confidence: 99%
“…Episodes of intense and prolonged drought are projected to surge worldwide due to future global warming/climate change [9]. Under drought stress, the inhibition of carbohydrate assimilation 2 of 14 or its export from sources organs may result in superfluous photosynthetic light energy, which may consequently induce the intense generation of reactive oxygen species (ROS) in leaves [10,11]. Subsequently, drought stress induces alterations in physiological status and disturbances in metabolism homeostasis, which deleteriously influence plant growth and development, including a marked suppression in the photosynthetic efficiencies of plants [12] and the depolarization of plasma membranes [13].…”
Section: Introductionmentioning
confidence: 99%
“…GPC-B1 is an NAC family transcription factor that accelerates leaf senescence and affects the protein, zinc, and iron contents of wild wheat grains [ 27 ]. TaNAMs were down-regulated by RNAi technology, which led to the stay-green phenotype and the reduction in nutritive material transport from flag leaves to seeds [ 38 ]. The difficulty that is associated with wheat gene studies is caused by the complexity of the huge wheat genome, with a high ratio of repeat sequences [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that TaNAM-RNAi plants maintained maximal photochemical e ciency modulated enzymatic network accompanied by low nitrogen and iron (Fe) concentration in ag leaf, suggesting that RNAi plants have more tolerance against Fe stress at certain level (Checovich et al, 2016). A quite similar pattern was also noted in the OsFRO1-RNAi plants.…”
Section: Overexpression Of Osfro1 Leads To Fe Overload Enhanced Ros A...mentioning
confidence: 73%